Ensayo sobre el uso de la encuesta: hermenéutica y reflexividad de la técnica investigativa - Ther Ríos, Francisco (Revista Austral de Ciencias Sociales, 2017)
This essay focuses on the validity, prestige and excessive use of the survey, as a tool, to measure a social reality. Using the so called social research of second order, it is clear that this technique has limited social application. First, I proceed to characterize the survey and to correlate its essence with power and hidden domination, I debate the process of how the sample is extracted, how subjects are silent and missing. Then, I debate the likelihood of this approach and modeling of society. I concentrate on the rationalization, control, duality, occult, and silence and continuity of the social milieu.